Evaluasi Bibliometrik Kinerja Sistem Dalam Meningkatkan Efisiensi Identifikasi Karyawan - Kusumah, Dadang Heri; Karyono, Karyono; Gunawan, Ahmad (Journal of Economic, Bussines and Accounting (COSTING), 2024)
In current workforce management, the integration of bibliometric systems has become a crucial strategy to streamline the employee identification process. This journal explores bibliometric analysis of existing literature to evaluate the performance of bibliometric systems in enhancing employee identification efficiency. Through a systematic examination of relevant studies, this research aims to provide insights into the current state of biometric technology, its applications, and its impact on workforce identification within organizational settings. The study employs bibliometric methods to assess the frequency and trends of key themes, technologies, and methodologies used in this field. The findings from this research offer a comprehensive understanding of advancements in biometric systems, their effectiveness in employee identification, and their implications for optimizing operational efficiency in contemporary workplaces.